A Phenomenological Study of EFL Teachers’ Experiences in Putting Multiliteracy Pedagogy through Online Teaching - Dina Handrayani; Nunung Suryati; Utari Praba Astuti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This research explored the implementation of multiliteracy pedagogy during online teaching in higher education. A qualitative method was used with interviews, observation, and document analysis. Five EFL teachers who taught reading and writing courses were the participants. Findings showed that the teachers utilized strategies in the class during online learning, like integrating students' prior knowledge with the new material, using students' and teachers' center methods, creating strategies to build students' critical thinking, and giving students projects. However, in scaffolding dimensions, some teachers argued that face-to-face learning was the more appropriate way to maximize scaffolding. Adapting the framework of the New London Group (1996), Kalantzis and Cope (2005), and Cope and Kalantzis (2015), the result indicated that five EFL teachers implemented multiliteracy pedagogy by using different strategies: creating an enjoyable environment in situated practice, utilizing many multimodalities in overt instruction, building students' critical thinking in critical framing, and existing knowledge and skills into students' project in transformed practice, and others. Based on the results, several suggestions will be valuable to future researchers: integrating multiliteracy pedagogy into other courses and investigating multiliteracy pedagogy in online and face-to-face learning.